PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN VIDEO ANIMASI TERHADAP MOTIVASI BELAJAR DAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Zahra Fadila; Ririn Andriani Kumala Dewi; Khoimatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by animated videos on students' learning motivation and critical thinking skills, as well as the effect of learning motivation on students' critical thinking skills. This study uses a quasi-experimental method with a pretest-posttest control group design. The population of this study was all NU Kaplongan Elementary School students in the 2024/2025 academic year, totaling 389 students. Using a simple random sampling technique, class VA was determined as the experimental class with 29 students and class VB as the control class with 30 students. Research data were collected through questionnaires and written tests. Based on the results of the independent sample t-test, the Sig. (2-tailed) value was 0.016. Because the Sig. (2-tailed) value was 0.016 <0.05, Ho was rejected and Ha was accepted. Based on the results of the independent sample t-test, the Sig. (2-tailed) value was 0.039. Because the Sig. (2-tailed) value is 0.039 < 0.05, Ho is rejected and Ha is accepted. Based on the results of the simple linear regression test, a Sig. of 0.044 is obtained. Because the Sig. value is 0.044 < 0.05, it can be concluded that learning motivation has an effect on critical thinking skills. Based on these results, it can be concluded that there is an influence of the Problem Based Learning (PBL) model assisted by animated videos on students' learning motivation and critical thinking skills, and there is an influence of learning motivation on students' critical thinking skills.